2016
DOI: 10.1371/journal.pone.0157504
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Modified Surface Enhances Osseointegration and Biomechanical Anchorage of Commercially Pure Titanium Implants for Bone-Anchored Hearing Systems

Abstract: Osseointegrated implants inserted in the temporal bone are a vital component of bone-anchored hearing systems (BAHS). Despite low implant failure levels, early loading protocols and simplified procedures necessitate the application of implants which promote bone formation, bone bonding and biomechanical stability. Here, screw-shaped, commercially pure titanium implants were selectively laser ablated within the thread valley using an Nd:YAG laser to produce a microtopography with a superimposed nanotexture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 63 publications
2
80
0
Order By: Relevance
“…[Kruyt et al submitted at O&N, under review] This was also found in pre‐clinical animal testing of this implant; however, removal torque measurements showed a 153% higher biomechanical anchorage of the laser‐modified implants. This underlines that ISQ might not reliably reflect actual osseointegration and that this implant might be beneficial for using in high‐risk patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…[Kruyt et al submitted at O&N, under review] This was also found in pre‐clinical animal testing of this implant; however, removal torque measurements showed a 153% higher biomechanical anchorage of the laser‐modified implants. This underlines that ISQ might not reliably reflect actual osseointegration and that this implant might be beneficial for using in high‐risk patients.…”
Section: Discussionmentioning
confidence: 95%
“…4.2 |Comparisons with other studies laser-modified implants 8. This underlines that ISQ might not reliably reflect actual osseointegration and that this implant might be beneficial for using in high-risk patients.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Here, we show that the overall MBL was significantly greater in smokers compared with non‐smokers as early as 90 days following implant installation. On the basis of experimental data and the fluctuation of ISQ values during healing in humans, it is likely that the greatest bone remodeling occurs during this very early time phase. Albeit speculative, the increased MBL in smokers during this early time phase might be related to different bone homeostasis in smokers, resulting in a net imbalance between the anabolic and catabolic pathways, favoring bone resorption.…”
Section: Discussionmentioning
confidence: 99%